Faktor Pembentuk Repurchase Intention Product Halal Food di Indonesia - suyono suyono; Indrianawati Usman; Sri Wahyuni Astuti (STIE Mandala Jember, 2023)
This article is a conceptual of several components that are antecedents of repurchase intention to halal products, halal products which in this case focus on traditional food or typical food in Surabaya. Typical food in Surabaya is served in various and unique forms, apart from being served in a unique form, the shape of this special food is very interesting with a taste that is of course very suitable for the palate of consumers, in this case young generations. Respondents in this study are expected to number more than 100 from East Java because the test used is structural equation modeling, in this test of course there needs to be a validity and reliability that must be fulfilled before goodness of fit is carried out. This research is still in the conceptual stage, of course it is hoped that there will be further research, so that a supportive suggestion will be found in this research in the form of continuing to preserve traditional culture by one of them consuming typical food. Keywords: halal product, repurchase, trust, TPB